A bi-level coordinated dispatch strategy for enhancing resilience of electricity-gas system considering virtual power plants. (May 2023) - Liu, Hanchen; Wang, Chong; Ju, Ping; Xu, Zhao; Lei, Shunbo
Highlights: The extreme-weather-induced cascading failures among subsystems are discussed. A bilevel resilient dispatch framework for the electricity-gas system is proposed. Stackelberg game is utilized for optimal discharging prices and schedules of EVs. Electricity-gas systems resilience is enhanced with the participation of VPPs. Impacts of VPPs on resilience of power grids and gas networks are illustrated. Abstract: As extreme weather disasters become more frequent and violent, there is grown emphasis on the resilience of electricity-gas systems, especially in preventing the extreme-weather-induced cascading failures among different subsystems. Meanwhile, with multiple advantages such as high flexibility, virtual power plants (VPPs) are gaining popularity, which shows their potential for providing advanced resilience services. Therefore, this paper proposes a bilevel coordinated dispatch strategy to utilize VPPs, consisting of battery storage devices and dispatchable electric vehicles (EVs), to enhance electricity-gas system resilience. Firstly, the Monte Carlo simulation method is adopted to simulate the probabilistic and sequential process of the extreme-weather-induced cascading failures between gas networks and power grids. Additionally, VPPs dispatch the battery storage through the direct control mode. Due to the price-sensitive nature of EVs, the interaction between VPPs and EV owners can be described as a Stackelberg game to determine the optimal discharging prices and schedule, which ensures the minimization of dispatch cost and the maximization of resilience and EVs owners' revenues. According to the Karush-Kuhn-Tucker optimality conditions, the bilevel game model can transform into single-level mix-integer linear programming. At last, the proposed model is applied to two case systems: a modified IEEE 30-bus system with an 11-node gas network and a modified IEEE 118-bus system with a 20-node gas network. And simulation results verify the effectiveness of the proposed model in enhancing electricity-gas system resilience against the cascading outages among subsystems through dispatching energy from virtual power plants.